2013
DOI: 10.1165/rcmb.2012-0291oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Migratory Inhibition Factor in Age-Related Susceptibility to Radiation Lung Injury via NF-E2–Related Factor–2 and Antioxidant Regulation

Abstract: Microvascular injury and increased vascular leakage are prominent features of radiation-induced lung injury (RILI), and often follow cancer-associated thoracic irradiation. Our previous studies demonstrated that polymorphisms in the gene (MIF) encoding macrophage migratory inhibition factor (MIF), a multifunctional pleiotropic cytokine, confer susceptibility to acute inflammatory lung injury and increased vascular permeability, particularly in senescent mice. In this study, we exposed wild-type and genetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Most recently, CD74 has been demonstrated in endothelial cells of patients with pulmonary HTN (43,44). Although the protective effect of MIF in endothelial cells has been described previously, the involvement of CD74 and its inducible expression as a consequence of hyperoxia are novel observations (6,22). An important limitation of this study is the lack of a mouse-specific monoclonal antibody that targets cell surface CD74.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Most recently, CD74 has been demonstrated in endothelial cells of patients with pulmonary HTN (43,44). Although the protective effect of MIF in endothelial cells has been described previously, the involvement of CD74 and its inducible expression as a consequence of hyperoxia are novel observations (6,22). An important limitation of this study is the lack of a mouse-specific monoclonal antibody that targets cell surface CD74.…”
Section: Discussionmentioning
confidence: 89%
“…One possibility is that this protection is mediated through increased antioxidant gene expression. Interestingly, a recent publication has suggested that silencing of MIF resulted in decreased NRF-2 activation, and hence, MIF would induce protection from oxidative stress-mediated damage (6). Multiple studies suggest that MIF provides protection from genotoxic stress and interferes with p53 and E2F-Rb signaling (19,60,61).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations